Indonesian peer to peer lending (P2P) at entrant's disruptive trajectory - Cliff Kohardinata; Noorlailie Soewarno; Bambang Tjahjadi (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Peer to peer (P2P) lending in Indonesia has been growing rapidly, therefore there is the potential for disruptive innovation processes in the financial sector. The aim of this study is to examine the impact of the growth of P2P lending on the growth of bank lending for micro, small and medium enterprises (MSME) and Non-MSME debtors. Separating the scale of the debtor is important, given the initial process of disruptive innovation of reaching areas that are not the incumbent's main target. The examination was conducted in this study using panel data regression, whereby the examination was done in stages. This was an overall examination without differentiating between the regions, further examination conducted with more detail by separating between the loans inside and outside Java Island. This is because the economic structure in Indonesia is still dominated by the regions in Java, but FinTech is generally able to grow in areas with less developed local economies. The result of this study is consistent overall, Java and outside Java Island, as shows that the growth in P2P lending in Indonesia does not have a significant impact on the growth of bank loans for Non-MSME lending. However, it does have a negative impact on the growth of bank loans for MSME lending. This is in line with the entrant's disruptive trajectory process by which the entrants enter the competition through an underserved market (niche markets) and not through the main target market of the incumbent (MSME).
Keywords: G21; G23; O33; 650; banking; disruptive innovation; FinTech; P2P lending; MSME; Non MSME